2013
DOI: 10.1021/cg401423d
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Growth of GaAs on Patterned Si(111) Substrates by Molecular Beam Epitaxy

Abstract: High-quality and defect-free GaAs were successfully grown via molecular beam epitaxy on silicon dioxide patterned Si(111) substrates by a two-step growth technique. Compared with the one-step approach, the two-step growth scheme has been found to be a better pathway to obtain a superior-quality GaAs on Si. Taking advantages of low energy for both Si(111) surface and GaAs/Si(111) interface, the two-step grown GaAs of total ∼175 nm atop patterned Si(111) substrates exhibits atomically smooth surface morphology, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 37 publications
1
17
0
1
Order By: Relevance
“…Despite this benefit, ART with cylinder hole masks has been investigated only by few research groups [48][49][50]. Hsu et al [48] reported the MOVPE growth of smooth continuous 900 nm thick GaAs layers of low defect density on Si(001) substrate patterned with a round nanohole SiO 2 mask having a hole diameter of 55 nm and aspect ratio of 4.7.…”
Section: Growth On Surfaces Patterned With a Cylinder Hole Maskmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite this benefit, ART with cylinder hole masks has been investigated only by few research groups [48][49][50]. Hsu et al [48] reported the MOVPE growth of smooth continuous 900 nm thick GaAs layers of low defect density on Si(001) substrate patterned with a round nanohole SiO 2 mask having a hole diameter of 55 nm and aspect ratio of 4.7.…”
Section: Growth On Surfaces Patterned With a Cylinder Hole Maskmentioning
confidence: 99%
“…Although Si(111) does not constitute the main substrate in complementary metal oxide semiconductor technology, a method for the growth of small GaAs layer volumes on Si(111) having structural and morphological characteristics highly attractive for applications has been developed: Chu et al [49] deployed a two-stage MBE growth to obtain monocrystalline GaAs with atomically smooth surface and low defect density in the openings of a SiO 2 hole mask on Si(111). The growth mechanism and thus the properties of the resulting layer can be understood as follows (Figure 16(a)): During the first low-temperature growth stage numerous small GaAs islands form by homogeneous nucleation, which then coalesce.…”
Section: Growth On Surfaces Patterned With a Cylinder Hole Maskmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3(a) is a typical AFM image of the SiO 2 mask, clearly showing a regular and repeatable nanohole pattern with a diameter of ~100 nm. After cleaned by standard RCA process [21], the patterned substrate was transferred to the MBE chamber for Mn x Ge 1-x nanodisks growth. After removing the native oxide layer at 950 °C for 10 mins, the substrate was cooled down to 250 °C for the Mn x Ge 1-x deposition with a Ge growth rate of ~0.2 Å/s.…”
Section: Nanolithography-patterned Mn X Ge 1-x Nanodisks By Mbementioning
confidence: 99%
“…Поэтому наиболее перспективным подходом для ре-шения вышеописанной проблемы является интеграция полупроводниковых соединений GaAs-группы с крем-нием [3]. Появление технологий формирования на по-верхности кремниевого чипа A III B V функциональных элементов создаст предпосылки для появления новых оптоэлектронных устройств с принципиально новой ар-хитектурой по сравнению с существующими комплемен-тарными структурами металл−оксид−полупроводник (КМОП) [4].…”
Section: Introductionunclassified